Changes in the value chain of dairy development in response to integrated extension interventions: The case of Atsbi-Wemberta District, Northern Ethiopia - Weldemariam, D. (Indira Gandhi National Open University, 2010)
A field study was conducted to assess the changes in response to the integrated interventions along the value chain of dairy production-marketing systems and to draw lessons for scaling out and up purposes. The changes associated with the interventions were systematically captured using household level surveys, key informant interviews and secondary sources in Atsbi-Womberta district, northern Ethiopia. The study was mainly based on a randomly sampled 100 dairy producers: 50 households with crossbred dairy cows and 50 households with local breed dairy cows. In the survey, key parameters and indicator variables that can indicate the changes in dairy performance along the value chain framework were collected and analyzed. Results show that the number of improved dairy cow breeds increased by about 5.56 fold and that of beneficiary households by 5.59 fold in 2009 compared to 2004 in the district. Similarly, the gross annual income of improved crossbred dairy cows beneficiaries households increased by 137% and that of local dairy cow breeds by 83% in 2009 compared to that of 2004. The changes in increased dairy productivity and gross income could attribute to introduction of improved dairy technologies (crossbred cows, feed development and health services), access to improved input supply, credit and market information. Most importantly, the changes attributed to the changes in skills and knowledge of dairy farmers on effective use of information on emerging market opportunities and response to challenges. In the district, the major changes have been in the shift from traditional diary management system where products mainly destined for home consumption to market oriented dairy husbandry. Under business type dairy husbandry, farmers’ capacity to use emerging dairy xiii market opportunities effectively and cope with emerging challenges need to be strengthened. Finally, the results clearly demonstrated that the link of improved dairy development to market brings immediate benefit to farmers and also enhanced the development of improved dairy farms in return. Thus, the lessons drawn from improved dairy development along the value chain framework need to be scale up and out within and outside the district.